Research on extraction method of ground fissures caused by mining through UAV image in coal mine areas - Qirang YANG; Zhenqi HU; Jiazheng HAN; Kun YANG; Yaokun FU (Meitan kexue jishu, 2023)
In order to promptly and exactly identify the mining ground fissures in coal mining areas, and avoid the secondary geological disasters, as well as restore the land ecological environment in the coal mining areas, this study focused on the extraction method of surface mining induced fissures, with the fissure development zone of coal mining face of Ningtiaota Coal Mine as the study area, which was located in the northwest of Shenmu County, Yulin City, Shaanxi Province. Meanwhile, the smooth execution of this research was based on low-altitude UAV remote sensing images, field surveys, and the construction of an object-oriented supervision classified model method. The images acquisition process was shown as follows: Firstly, the candidate segmentation parameters were obtained utilizing the ESP（Estimation of scale parameter）optimal segmentation scale evaluation tool, and then the optimal segmentation parameters were determined immediately combining visual interpretation, finally the image objects such as fissures and vegetation were obtained. 15 optimized feature parameters were determined from 24 initial feature sets to construct the optimized feature set with the feature space optimization tool. On this basis, a variety of machine learning classifier models were combined, such as Support Vector Machine, K Nearest Neighbor, Random Forest, Naive Bayes, etc. The experimental analysis results presented that the classification effect and accuracy of the land features were consistent. The SVM classification method had the best overall effect, performing best in the four erroneously partitioned domains, with the least number of misclassified small patches. The overall classification accuracy achieved 88.97%, and the Kappa coefficient attained 0.849. In addition, the F1 value of crack extraction accuracy reached 87.87%, with the Kappa coefficient amount to 0.848. The overall classification accuracy of the four classification methods was above 80%. The optimal model method accurately extracted 10 main fissures in the research area, which was more efficient than traditional manual vectorization. The surface mining fissures could be effectively extracted by the aid of low-altitude drone remote sensing images and object-oriented methods. This research could provide technical support for the investigation and monitoring of geological disasters caused by coal mining subsidence and land ecological restoration.